(untitled) (Communications in Computational Physics, 2020)
A coupled model, capable of simulating transonic flow, solid heat conduction, species transport, and gas radiation, is developed that provides better computational treatment of infrared radiation from hot exhaust nozzles. The modeling of gas radiation is based on a statistical narrow-band correlated-k analysis, whose parameters are deduced from the HITEMP line-by-line database. To improve computational efficiency, several methods are employed. A mixed analytical-numerical algorithm is described for the stiffness of the two-equation turbulence model and an alternating direction implicit pretreatment for the ill-conditioned matrix appearing in the coupled problem of flow and solid heat conduction. Moreover, an improved multigrid method and a symmetry plane treatment of the radiation transfer-energy equations are also introduced. Four numerical simulations are given to confirm the efficiency and accuracy of the numerical method. Finally, an account of the aerothermodynamics and infrared characteristics for two types of nozzles are presented. The infrared radiation intensity of the Chevron ejecting nozzle is clearly smaller than that of the common axisymmetric ejecting nozzle. All computations can be performed on a personal computer.